Prediction of stability constants of Cu2+ complexes with organic fluorescent ligands using thermodynamic cycle in combination with DFT theory and SMD solvent model - Bay, Mai Van; Hien, Nguyen Khoa; Thanh, Hoang Kim; Nam, Pham Cam; Quang, Duong Tuan (Hue University Journal of Science: Natural Science, 2020)
Accurately predicting the stability constant ( ) of the Cu2+ complex with organic fluorescent ligands provides an important basis to design molecular fluorescent sensors for selective detection of Cu2+. With appropriate reference complexes, the calculated stability constants are in good agreement with experimental values. The values of the predicted stability constants of Cu2+ complexes with Calcein blue (H3Cb) and FluoZin-1 (H2Fz) are 13.33 (exp. 14.27) and 6.59 (exp. 6.01), respectively. More importantly, the results could be applied to the investigation of complexes.